TRP channels: Intestinal bloating TRiPs up pathogen avoidance. (September 2021) - Ronan, Elizabeth A.; Xiao, Rui; Xu, X.Z. Shawn
Highlight: Using C. elegans as a model, a new study demonstrated that two TRPM channels sense pathogen colonization-induced intestinal distension. Pathogen-induced intestinal distension triggers fast pathogen avoidance behavior, thereby limiting pathogen infection . These findings reveal a novel role of the evolutionarily conserved TRPM channels in gut physiology and pathogen defense. Abstract: Transient receptor potential (TRP) channels are expressed in many nonneural tissues where their functions are not well known. Using C. elegans as a model, a new study demonstrated that colonization of the Gram-positive pathogenic bacteria E. faecalis in the intestine causes intestinal distention. Two TRPM channels sense such intestinal distension to trigger fast pathogen avoidance behavior, thereby limiting pathogen infection . This work signifies the novel role of TRP channels in gut physiology and pathogen defense.